2013
DOI: 10.1210/en.2012-1834
|View full text |Cite
|
Sign up to set email alerts
|

Central Ghrelin Signaling Mediates the Metabolic Response of C57BL/6 Male Mice to Chronic Social Defeat Stress

Abstract: Chronic stressors promote metabolic disturbances, including obesity and metabolic syndrome. Ghrelin, a peptide that promotes appetite and the accumulation of adipose tissue, is also secreted in response to stressors to protect the brain and peripheral tissues from the effects of these stressors. Here we demonstrate that elevated ghrelin levels produced by chronic exposure to social stress are associated with increased caloric intake and body weight gain in male C57BL mice. In contrast, stressed mice lacking gh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
153
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(161 citation statements)
references
References 59 publications
6
153
2
Order By: Relevance
“…Similar to previously published data in strains not genetically predisposed to obesity (Patterson et al 2013;Sanghez et al 2013; Table 2), the current results further support the multistage and polygenic nature of T2D and suggest that the disease develops in the presence of multiple risk factors. In mouse strains of different genetic backgrounds, we and others showed that CSS aggravates diet-induced obesity and caused hypoactivity and hyperphagia (Table 2; Bartolomucci et al 2005Bartolomucci et al , 2009Dadomo et al 2011;Patterson et al 2013;Razzoli et al 2015a, b).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Similar to previously published data in strains not genetically predisposed to obesity (Patterson et al 2013;Sanghez et al 2013; Table 2), the current results further support the multistage and polygenic nature of T2D and suggest that the disease develops in the presence of multiple risk factors. In mouse strains of different genetic backgrounds, we and others showed that CSS aggravates diet-induced obesity and caused hypoactivity and hyperphagia (Table 2; Bartolomucci et al 2005Bartolomucci et al , 2009Dadomo et al 2011;Patterson et al 2013;Razzoli et al 2015a, b).…”
Section: Discussionsupporting
confidence: 92%
“…Finally, subordinate db/db mice showed a systemic lowgrade pro-inflammatory profile, as suggested by elevation of TNF-alpha levels and mild increase in IL-6 levels, in line with results in wild-type mice (Patterson et al 2013). Adipose tissue in obese and diabetic individuals might develop an inflammatory milieu which ultimately leads to insulin resistance (Patel et al 2013).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations